Decreasing prevalence of retinopathy in childhood‐onset type 1 diabetes over the last decade: A comparison of two cohorts diagnosed 10 years apart - Salardi, Silvana; Porta, Massimo; Maltoni, Giulio; Bassi, Marta; Minuto, Nicola; D'Annunzio, Giuseppe; Baltatescu, Tamara; Ariaudo, Maria; Zucchini, Stefano; Levantini, Gabriella; Tumini, Stefano; Franceschi, Roberto; et al. (Diabetes, obesity & metabolism, 2021)
Aim To ascertain whether the prevalence of retinopathy has declined over the last 2 decades in individuals with childhood‐onset type 1 diabetes and whether this might be explained by changes in lifetime HbA1c. Materials and Methods A multicentre, retrospective, observational study, comparing 128 subjects with diabetes onset in 2000‐2003 assessed for retinopathy in 2016‐2019, with a previous cohort of 115 individuals diagnosed in 1990‐1993 and assessed for retinopathy in 2007‐2009, was conducted. The two cohorts had both a similar diabetes duration and age at diagnosis. Retinal photographs were centrally graded. Lifetime HbA1c and its variability, estimated as the ratio between intrapersonal mean and standard deviation of HbA1c, were evaluated. Results The prevalence of any retinopathy in the new and old cohort was 24.2% and 43.5% (P < .003), respectively, and that of severe retinopathy was 1.7% and 9.6% (P = .018). Lifetime HbA1c was lower in the new cohort (7.8% ± 0.8% vs. 8.1% ± 0.8%; P = .002) during all periods following the first 5 years after diagnosis. Patients without retinopathy in the two cohorts had similar levels of HbA1c. Compared with patients without retinopathy, those with retinopathy had higher lifetime HbA1c and long‐term HbA1c variability. However, on multiple regression analysis, only lifetime HbA1c was independently associated with retinopathy (P = .0018). Conclusions The risk of developing retinopathy was nearly halved in children who developed type 1 diabetes in the new millennium compared with previous cohorts. These results confirm that maintaining the lowest possible levels of HbA1c throughout lifetime protects from diabetic retinopathy.